Carbon emissions pinch analysis (CEPA) for energy sector planning in Nigeria - Salman B.; Nomanbhay S.; Foo D.C.Y. (Springer Verlag, 2023)
Carbon dioxide; Emission control; Energy policy; Fossil fuels; Renewable energy resources; Carbon emissions reductions; Electricity generation; Emissions reduction; Energy planning; Energy sector planning; Power sector; Renewable energy applications; Sustainable management; Carbon